Stressors and coping strategies among physiotherapy students: Towards an integrated support structure - Elizabeth C. Janse van Vuuren; Karen Bodenstein; Mariette Nel (AOSIS, 2018)
Background: Stress is a major problem among university and, specifically, health care students, as it may influence academic performance and psychological well-being negatively. Aims: To develop and implement a student support system based on the perceived stress, stressors and coping strategies of physiotherapy students.   Methods: A cross-sectional, descriptive study was undertaken, using a literature-based, selfcompiled questionnaire and the 28-item General Health Questionnaire (GHQ-28). Over a period of three years, 207 third- and fourth-year physiotherapy students at a South African university were included.   Results: Psychological distress was experienced by 61.8%-71.2% of participants. During the 3 months prior to the study, 6% of participants received psychological or psychiatric help and 9% of participants used some form of psychiatric medication. The main stressors identified during clinical training were the suffering and death of patients, academic pressure and tension during interaction with personnel. Participants indicated that they mainly coped with these stressors by talking to someone such as a family member or a friend.   Conclusions: Based on the findings of this study, a framework to identify and support students in pre-clinical and clinical training years was developed and implemented over five years. This proposed framework might positively contribute to the psychological well-being of health care students.